Inovasi Kuliner Lokal Ketela Ungu sebagai Breakfast Di Desa Wisata Sangkan Gunung - Ida Ayu Elistyawati; I Gusti Made Wendri; Ni Made Rai Sukmawati; Ni Putu Wiwiek Ary Susyarini (Jurnal Pemberdayaan Ekonomi, 2022)
Purpose: Improving the skill of Pokdarwis members to make innovation in processing the breakfast menu ketela ungu. The food processing is based on the farm produce yielded in local farming, for increasing the selling value of the farm produce. Method: This training uses the socialization method as well as the technique of ketela ungu processing producing ‘bubuh sumsum’, ‘giling-giling’, ‘batun salak’ and ‘ongol-ongol’ as item of breakfast. Participant Assesment: The assessment is based on the participants’ involvement on the training. Result: The output of the training includes; “bubur sumsum’, ‘giling-giling’, ‘batun salak’, and ‘ongol-ongol’ as breakfast menu. These menu are served to the visitors visiting the village. Limitation: This training is to improve participants skill in processing ketela ungu as breakfast menu Contribution: In the form of training on breakfast menu is able to increase the competitiveness of human rresources in serving of breakfast menu , local culinary.